2018
DOI: 10.1002/ange.201807270
|View full text |Cite
|
Sign up to set email alerts
|

All‐Inorganic CsPb1−xGexI2Br Perovskite with Enhanced Phase Stability and Photovoltaic Performance

Abstract: Compared with organic‐inorganic perovskites, all‐inorganic cesium‐based perovskites without volatile organic compounds have gained extensive interests because of the high thermal stability. However, they have a problem on phase transition from cubic phase (active for photo‐electric conversion) to orthorhombic phase (inactive for photo‐electric conversion) at room temperature, which has hindered further progress. Herein, novel inorganic CsPb1−xGexI2Br perovskites were prepared in humid ambient atmosphere withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In the mixed-halide CsPbI 3-x Br x perovskites, it was found that CsPbI 2 Br has not only a suitable bandgap of 1.92 eV but also a considerably high ambient stability, implying that the composition engineering would be an effective strategy for stabilizing crystal [18]. Moreover, there have been many metal cations with smaller ionic radii including K + , Mn 2+ , Co 2+ , Zn 2+ , Ge 2+ , Sr 2+ , Eu 2+ and Ba 2+ introduced into the interstitial or substitutional sites of cesium lead halide perovskites, with various purposes like enhancing phase stability, manipulating crystallization process, passivating defects, optimizing energy band, suppressing ion migration, improving optoelectronic properties, etc [19][20][21][22][23][24][25][26]. It is worth noting that some experimental results showed that the alkali metal ion K + prefers to substitute for Cs + , while some other researches proved from both experimental and theoretical perspectives that K + ions are energetically to occupy the interstitial sites of perovskite lattices such as MAPbI 3 , FAMAPbI 2 Br, (FAPbI 3 ) 0.875 (CsPbBr 3 ) 0.125 and so on [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In the mixed-halide CsPbI 3-x Br x perovskites, it was found that CsPbI 2 Br has not only a suitable bandgap of 1.92 eV but also a considerably high ambient stability, implying that the composition engineering would be an effective strategy for stabilizing crystal [18]. Moreover, there have been many metal cations with smaller ionic radii including K + , Mn 2+ , Co 2+ , Zn 2+ , Ge 2+ , Sr 2+ , Eu 2+ and Ba 2+ introduced into the interstitial or substitutional sites of cesium lead halide perovskites, with various purposes like enhancing phase stability, manipulating crystallization process, passivating defects, optimizing energy band, suppressing ion migration, improving optoelectronic properties, etc [19][20][21][22][23][24][25][26]. It is worth noting that some experimental results showed that the alkali metal ion K + prefers to substitute for Cs + , while some other researches proved from both experimental and theoretical perspectives that K + ions are energetically to occupy the interstitial sites of perovskite lattices such as MAPbI 3 , FAMAPbI 2 Br, (FAPbI 3 ) 0.875 (CsPbBr 3 ) 0.125 and so on [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…2 This motivates recent efforts to develop new photovoltaic cells that are based on nontoxic perovskite halides, where Pb 2+ is replaced with Sn 2+ and/or Ge 2+ . [3][4][5][6][7] From a fundamental standpoint, the fascinating optoelectronic properties of HPs are closely related to their highly anharmonic thermal motions that lead to local, polar fluctuations and thus, localization of charge carriers. [8][9][10][11]75 The perovskite crystal (with stoichiometry AMX 3 ) consists of a three-dimensional network of corner-sharing MX 6 octahedra, with A-site cations occupying the cuboctahedral voids.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Poly(3‐hexylthiophene) (P3HT), which is inexpensive and exhibits excellent hole mobility, has been used as an alternative dopant‐free hole transport material (HTM). [ 22,23 ] The unencapsulated P3HT‐based devices with a CsPbI 2 Br active layer maintained ≈95% of their initial PCE after 1300 h of storage in ambient conditions. [ 24 ] Tian et al.…”
Section: Introductionmentioning
confidence: 99%